Instrucción materna y condiciones de salud en ninos desnutridos de la Plata, Buenos Aires, Argentina - Ortale, María Susana; Sanjurjo, Adriana; Osimani, Nidia; Rodrigo, Adelaida (1998)
Se analiza la asociacion de la instruccion materna variable independiente con las condiciones de salud de ninos desnutridos bajo Programa de Asistencia Integral que se desarrolla en la Unidad de Rehabilitacion Nutricional del Hospital de Niños de La Plata (URN). De la poblacion asistida en la URN, se seleccionaron 82 ninos de O a 4 anos de edad con desnutricion de causa primaria atendidos entre marzo y noviembre de 1997. Fueron evaluados los parametros PIE, PIT y TIE segun las tablas de referencia nacionales. Se consideraron al ingreso las siguientes características: peso al nacimiento, duracion de la lactancia, cumplimiento del esquema de vacunacion, presencia de enfermedades intercurrentes y hospitalizaciones previas. Los valores hallados en estos parametros se comparan con datos poblacionales y con aquellos fijados como meta nacional. El grupo estudiado presenta desnutricion post-natal temprana moderada y leve, (32 porciento recibió lactancia materna como alimentación exclusiva hasta el cuarto mes). Es elevado el numero de intercurrencias previas, presentando el 50 de los casos hospitalizaciones y vacunacion incompleta. Mas de la mitad de las madres carece de instruccion o tienen primaria incompleta. No obstante instruccion materna y la salud infantil no arrojan diferencias estadisticamente significativas.
We analyze the association of maternal instruction and health conditions of undemourished children within the Integral Assistance Program developed by the Nutritional Rehabilitation Unit of La Plata Children Hospital (NRU). From the population attended at the NRU, between March and Novernber, 1998, 82 0-4 year old children with primary undemutrition were selected. The parameters assessed were weightlage, weightheight, and heightfage, following the national reference tables. At admission, the following characteristics were taken into account: birth weight, period of breast feed, vaccine scheme fulfilled, presence of diseases, and previous hospitalizations. From the mothers social and ecionomical survey, the mother instruction was selected as an independent variable for this study, in order to check if it has the same relevmce in children health conditions that the one found in populaticin studies. The values obtained for these parameters are compared with population data, and with those values established as a national goal. The group under study presents early postnatal undernutrition, vveak or moderate; 32porciento of them received breast feed as exclusive food up to the fourth month. The number of previous diseases is high, with 50 of hospitalization and incomplete vaccine scheme. However, confronting the proposed hypothesis, the association of this variable with the specific characteristics of children health evaluated at admission does not show statistically significant differences within the groiip under study.
Keywords: Desnutrición primaria; Instruccion materna; Salud infantil; Primary undemutrition; Maternal instruction; Children health